Influence of temporal and spectral profiles of lasers on weld quality of titanium. (November 2020) - Mohanta, Antaryami; Leistner, Matthias; Leparoux, Marc
Highlights: Effect of interaction of lasers having different temporal and spectral profiles with titanium on weld surface quality investigated by high-speed imaging and optical emission spectroscopy. Role of temporal and spectral profiles of the lasers on plume dynamics. Dark colouration around the laser spot on the weld surface due to reabsorption of the laser pulse by neutral titanium atoms in the plume. Achievement of clean weld surface by nullifying the reabsorption process. Abstract: The effect of interaction of lasers having different spectral and temporal profiles with titanium on the weld surface quality is investigated by high-speed imaging and optical emission spectroscopy at atmospheric pressure in argon environment. High-speed imaging of the plume reveals that plume is produced during the laser pulse. Decrease in plume size and expansion rate is observed for those lasers whose spectral profiles overlap with more number of neutral atomic titanium transitions (Ti I) owing to increasing rate of reabsorption of the laser pulse primarily by the neutral titanium atoms present in the plume. Darkness around the laser spot on the titanium surface observed due to deposition of the nanoparticles increases with decrease in size and expansion rate of the plume which indicates that reabsorption of the laser pulse is the main cause of dark colouration of the surface. The bright appearance of a part of the plume produced by one laser at which another laser whose spectral profile cover many Ti I transitions is passed confirms the reabsorption process. Clean appearance of the surface around the laser spot along with enhancement of the plume size and expansion rate is observed for lasers with customized spectral profiles which do not overlap with any Ti I transitions. Modulation of the temporal profile can moderately improve the plume expansion rate and reduce the darkness around the laser spot provided that the laser spectral profile does not overlap with many Ti I transitions, particularly, with those whose energy of lower levels is less than 3 eV.